Interaction of polymorphisms in APOA4-APOA5-ZPR1-BUD13 gene cluster and sleep duration on 5-year lipid changes in middle aged and older Chinese. Issue 8 (29th May 2019) - Yang, Liangle; Ma, Lin; Guo, Wenting; Fang, Qin; Lai, Xuefeng; Zhang, Xiaomin
Abstract: Study Objectives: Lipid profiles are influenced by both genetic and environmental factors. Genetic variants in the APOA4-APOA5-ZPR1-BUD13 gene cluster and aberrant sleep duration were independently identified to be associated with lipids in previous studies. We aimed to investigate whether sleep duration modified the genetic associations with longitudinal lipids changes. Methods: Four single nucleotide polymorphisms (SNPs), rs17119975, rs651821, rs7396835, and rs964184 in the APOA4-APOA5-ZPR1-BUD13 gene cluster were genotyped among 8648 apparently healthy subjects from the Dongfeng-Tongji (DFTJ) cohort. Information on sleep duration was obtained by questionnaires. Changes in total cholesterol, triglyceride, high-density lipoprotein cholesterol (HDL-c), low-density lipoprotein cholesterol (LDL-c), were evaluated from baseline to 5-year follow-up. Results: After multivariate adjustments, we found that rs651821 and weighted genetic risk score (GRS) were significantly associated with increased triglyceride, and the genetic association with triglyceride change consistently strengthened across sleep duration categories. The differences in triglyceride changes per increment of risk allele for rs651821 were 0.028 ( SE = 0.017, p = 0.112), 0.051 ( SE = 0.009, p < 0.001), and 0.064 ( SE = 0.016, p < 0.001) in individuals with sleep duration ≤7, >7–<9, and ≥9 h, respectively ( p interaction = 0.031). The GRS also showed a significant interaction with sleep duration categories for triglyceride change ( p interaction = 0.010). In addition, all of the four SNPs and GRS were inversely related to HDL-c changes. Conclusions: Longer sleep duration might exacerbate the adverse effects of SNPs in APOA4-APOA5-ZPR1-BUD13 gene cluster on 5-year triglyceride changes.